P385 SYNCOPAL VENTRICULAR TACHYCARDIA IN HEALTHY HEART: AN UNUSUAL ORIGIN!. (18th May 2022) - Astegiano, M; Pasquero, M; Ruffini, S; Franco, E; Iancu, D; Moretti, C
Abstract: Torsade de pointes is a particular type of ventricular tachycardia, characterized by QRS complexes that vary progressively in amplitude and morphology, giving the impression of oscillating around the isoelectric line. Causes include long QT syndrome (congenital or drug–induced) or severe hypomagnesemia. We report the case of a 57–year–old woman, a smoker, with a history of weight loss in the last 6 months, hospitalized in Medicine for marked asthenia and an episode of fleeting loss of consciousness, from sitting. She was asymptomatic for chest pain. The physical examination showed a pathological thinness, with BMI 15 kg/m2, rhythmic cardiac activity, no murmurs, no signs of decompensation, flat abdomen, not enlarged liver. Pale, dry skin was observed. On ECG: sinus rhythm, HR 70 bpm, QTc slightly increased 0.47 sec, flat T wave in lateral. Blood exams evidenced: hypokalemia, hypomagnesemia, rise of the amylase. On the MRI abdomen we found large inhomogeneous areas on the head and body of the pancreas, referable to the picture of focal pancreatitis. For syncopal episode during hospitalization in Medicine, she was transferred in Cardiology, where, during electrocardiographic monitoring, paroxysmal ventricular tachycardias torsade de pointes–like, symptomatic, self–resolved was registered. We diagnosed an acute pancreatitis with typical radiological characteristics of an autoimmune form, determining severe electrolyte imbalance and consequent symptomatic paroxysmal ventricular tachycardias. Oral magnesium supplement and corticosteroid therapy allowed the resolution of the arrhythmic problem, monitored over time through the implantation of a loop recorder.